Severe Unusual Presentation of Fat Necrosis in Neonatal Age: A Case Report - Shatha M. Albokhari; Nouran M. Abu-Ouf (Journal of King Abdulaziz University: Medical Sciences, 2023)
Fat necrosis in newborns is estimated to be a rare and self-healing (limited) condition that affects full term or post term newborns in the first few weeks of life. The etiology is not clear and even then this disorder is linked with hypothermia, thrombocytopenia, anemia, gestational diabetes, neonatal hypoxia, and obstetric trauma, preeclampsia and maternal exposure to cocaine or calcium channel blockers usage at the time of pregnancy. Hypercalcemia is considered the most serious, albeit rare, complication appearing a maximum six months after skin lesions.